Morphological and Molecular Identification of Helopeltis Species on Cocoa from Kaliwining Experimental Station, Jember, Indonesia - Aldini, Gracia Melsiana; Rahma, Anisa Aulia; Budiman, Aris (Pelita Perkebunan (a Coffee and Cocoa Research Journal), 2023)
Severe crop loss of cocoa in Indonesia has long been reported to be caused by Helopeltis. It has been noted that cocoa and Helopeltis have existed in Kaliwining Experimental Station of Indonesian Coffee and Cocoa Research Institute (ICCRI), Jember, Indonesia, for about 100 years, and the species have developed during that time. Our study aimed for examining the Helopeltis species that attacked cocoa in this experimental station both morphologically, morphometrically, and molecularly and to compare the species with the one attacking cocoa in Java and Nusa Tenggara, preserved at the GenBank. Helopeltis was sampled from infested cocoa pods collected representatively from cocoa at the Kaliwining ES and then reared in the Crop Protection Laboratory of ICCRI. Adults of Helopeltis laboratory-reared insects were identified, 30 females 30 males were selected. Weexamined the morphology and morphometry of the samples, and their identifica tion was based on an insect identification key. Morphometry measurement of male and female body parts includes body length, antenna segments, head, eyes, collar, wing, tibia, and femur. In addition, the molecular identification of Helopeltissp. was made through DNA extraction, amplification, and sequence analysis of DNA target regions using the COI part of mitochondrial DNA. External morphological identification, supported by morphometry of the Helopeltis specimen from Kaliwning, the white bands on all femora, body length, and the ratio of the firstantennal segment to the posterior width of the pronotum suggested that the insect belongs to Helopeltis bradyi. Similarly, molecular identification using PCR amplification through specific primers from COI gene sequences confirmed that Helopeltis specimens from Kaliwining are classified as Helopeltis bradyi.